Stator Inter-turn Fault Detection in Inverter Fed Induction Motor Drives - Khadim Moin Siddiqui; Kuldeep Sahay; V. K. Giri (Institute of Advanced Engineering and Science, 2017)
The Squirrel Cage Induction Motor (SCIM) with advanced power electronic inverters presents the greater advantages on cost and energy efficiency as compared with other industrial solutions for varying speed applications. In recent, the inverter fed induction motors are being popular in the industries. These inverter fed-motors are recently gathering great recognition for multimegawatt industrial drive applications. In this present paper, a dynamic simulation model of PWM inverter fed SCIM with direct torque control jointly has been presented and analyzed in the recent MATLAB/Simulink environment. From the proposed simulation model, the transient behavior of SCIM has been analysed for healthy as well as for stator inter-turn fault condition. The dynamic simulation of induction motor is one of the key steps in the validation of design process of the electric motor and drive system. It is extremely needed for eliminating probable faults beforehand due to inadvertent design mistakes and changes during operation. The simulated model gives encouraging results with reduced harmonics [1]. By using the model, the successful detection of stator inter-turn fault of the SCIM is carried out in the transient condition. Therefore, early stator fault detection is possible and may avoid the motor to reach in the catastrophic conditions. Therefore, may save millions of dollars for industries.